OMISSIONS AND ADDICTIONS DURING NOTE-TAKING AT SIMULTANEOUS INTERPRETING PROCESSES - Allambergenova Umida Muratbayevna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The article explores the common issues of omissions and additions in note-taking during simultaneous interpreting. It discusses the causes of these errors, including cognitive overload, speaker speed, and misinterpretation, as well as their consequences. The article also highlights strategies to balance accuracy and brevity in note-taking, such as training, active listening, memory enhancement techniques, and the use of technology.